(123) I-2β-carbomethoxy-3β-(4-iodophenyl)-N-(3-fluoropropyl) nortropane single photon emission computed tomography and (123) I-metaiodobenzylguanidine myocardial scintigraphy in differentiating dementia with lewy bodies from other dementias: A comparative study - Tiraboschi, Pietro; Corso, Angelo; Guerra, Ugo Paolo; Nobili, Flavio; Piccardo, Arnoldo; Calcagni, Maria Lucia; Volterrani, Duccio; Cecchin, Diego; Tettamanti, Mauro; Antelmi, Luigi; Vidale, Simone; Sacco, Leonardo; et al. (Annals of neurology, 2016)
To compare the diagnostic value of striatal (123) I-2β-carbomethoxy-3β-(4-iodophenyl)-N-(3-fluoropropyl) nortropane ((123) I-FP-CIT) single photon emission computed tomography (SPECT) and (123) I-metaiodobenzylguanidine ((123) I-MIBG) myocardial scintigraphy in differentiating dementia with Lewy bodies (DLB) from other dementia types. This prospective longitudinal study included 30 patients with a clinical diagnosis of DLB and 29 patients with non-DLB dementia (Alzheimer disease, n = 16; behavioral variant frontotemporal dementia, n = 13). All patients underwent (123) I-FP-CIT SPECT and (123) I-MIBG myocardial scintigraphy within a few weeks of clinical diagnosis. All diagnoses at each center were agreed upon by the local clinician and an independent expert, both unaware of imaging data, and re-evaluated after 12 months. Each image was visually classified as either normal or abnormal by 3 independent nuclear physicians blinded to patients' clinical data. Overall, sensitivity and specificity to DLB were respectively 93% and 100% for (123) I-MIBG myocardial scintigraphy, and 90% and 76% for (123) I-FP-CIT SPECT. Lower specificity of striatal compared to myocardial imaging was due to decreased (123) I-FP-CIT uptake in 7 non-DLB subjects (3 with concomitant parkinsonism) who had normal (123) I-MIBG myocardial uptake. Notably, in our non-DLB group, myocardial imaging gave no false-positive readings even in those subjects (n = 7) with concurrent medical illnesses (diabetes and/or heart disease) supposed to potentially interfere with (123) I-MIBG uptake. (123) I-FP-CIT SPECT and (123) I-MIBG myocardial scintigraphy have similar sensitivity for detecting DLB, but the latter appears to be more specific for excluding non-DLB dementias, especially when parkinsonism is the only "core feature" exhibited by the patient. Our data also indicate that the potential confounding effects of diabetes and heart disease on (123) I-MIBG myocardial scintigraphy results might have been overestimated. Ann Neurol 2016;80:368-378.